Pengaruh Diskon, Ongkir, dan Ontime Delivery Terhadap Keputusan Pembelian: Survei Konsumen Gofood di Jabodetabek - Muhammad Ahzami Amin; Aminah Nuriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of Discount, Shipping Cost, and Ontime Delivery on the Purchase Decision of GoFood consumers in the Jabodetabek area.The research adopts a descriptive quantitative approach involving 428 GoFood users. Data were collected through questionnaires and analyzed using SPSS with multiple linear regression tests, t-tests, F-tests, and the coefficient of determination (R²). Discount, Shipping Cost, and Ontime Delivery each have a positive and significant effect on purchase decisions. Simultaneously, the three variables also have a significant effect (F = 460.492), contributing 76.5% to purchase decisions, while the remaining 23.5% is influenced by other factors beyond this study. These findings indicate that the three variables are dominant factors influencing GoFood consumer purchase decisions in Jabodetabek.